The Role of Non-Formal Education in Strengthening Students' Moral Character - Aprilia, Nindy Putri; Fakhruddin, Agus; Hermawan, Wawan (Journal of Islamic Education Students (JIES), 2024)
This study aims to examine the role of non-formal education in strengthening students' moral character through programs at Madrasah Diniyah Takmiliyah Al-Karimah. Using a qualitative descriptive approach, data were gathered through observation, interviews, and documentation. The findings indicate that curriculum optimization and the implementation of programs like Thursday Berinfaq, Friday Berkah, and gender-based activities significantly contribute to character development among students. Additionally, teachers serve as essential role models, facilitating the internalization of moral values in students' everyday lives. These findings underscore the importance of collaboration between educational institutions and teachers to support effective and sustainable moral education.┬á┬á